Childfree in Marriage: An Islamic Family Law Analysis from the Perspective of Maqashid al-Shariah - Sarkowi; Muhammad Maghfur Agung (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
The childfree phenomenon has become a contemporary issue that is increasingly developing among young couples, including within Muslim communities. The decision of married couples not to have children has generated debate from the perspective of Islamic family law, particularly regarding the objectives of marriage and the principles of maqashid al-shariah. This study aims to analyze the childfree phenomenon from the perspective of Islamic family law using the maqashid al-shariah approach. The research method employed is library research with normative-juridical and philosophical approaches. Data were obtained from classical and contemporary literature, scientific journals, and Islamic family law regulations. The results of the study indicate that childfree is not explicitly prohibited in Islam; however, it must be analyzed based on the objectives of marriage and maqashid al-shariah, particularly hifz al-nasl (the preservation of lineage). The decision to be childfree may be permissible under certain conditions, such as health, psychological, or urgent economic factors, but it is not recommended if it contradicts the primary objectives of marriage in Islam. Therefore, childfree is considered an ijtihadi and contextual decision that must take into account public benefit (maslahah) and the principles of maqashid al-shariah.